Religious Habituation dalam Menstimulasi Intelegensi Nilai Agama dan Moral Anak Usia Dini - Badriyah, Lailatul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
Abstract: Seeing the phenomenon that exists in today's society, that the moral depravity of adolescents and school-age children is the lack of attention to religious education. The results of his research are Religious Habituation or religious habituation in stimulating NAM intelligence (religious and moral values) of students at Al Mubarok PAUD, Nglawak Village, Prambon District, Nganjuk Regency. While the process is through the following stages: (1) Planning for the Al Mubarok PAUD school program using the Covid-19 Emergency curriculum in carrying out activity planning (2) Implementation of religious habituation activities during the COVID-19 pandemic is Learning from Home (BDR) whose mentoring is carried out by classroom teachers collaborating with student guardians via online (via WA groups of community guardians and homeschoolers) From the results of the study it was found that the effectiveness of activities through a combination of online and offline (taking and collecting assignments) was more in demand by the parents of PAUD Al Mubarok. (3) Evaluations and reflections carried out by classroom teachers were reported to the principal and guardians of students through activity report books (link books), report cards and portfolios (children's work).